Weekend versus Weekday Procedures for Total Hip Arthroplasties - Okpara, Shawn; Ghali, Abdullah; Momtaz, David; Cushing, Tucker; Kotzur, Travis; Han, Albert; Mitchell, Parker; Pearl, Adam; Bora, Varun; Seifi, Ali; Saleh, Khaled J. (The Journal of Hip Surgery, 2023)
The “weekend effect” is the phenomenon that claims increased adverse outcomes for weekend procedures compared to weekday procedures. However, there is significant controversy regarding such disparities in elective orthopaedic surgeries. With the increasing demand for hip arthroplasty projected over the next 20 years, it is important to investigate a possible “weekend effect” to optimize outcomes and cost-effectiveness. In this study, we investigate the association between weekday versus weekend total hip arthroplasty (THA) and postoperative outcomes using the Healthcare Cost and Utilization Project (HCUP) data. We performed a retrospective analysis of the HCUP database between 2002 and 2020 comparing THAs done Monday to Friday versus THAs done Saturday to Sunday. Data collected included patient demographics and comorbidities, hospital length of stay, admission to procedure time, discharge disposition, mortality, and outcome data through postoperative day 30. THAs performed on weekends were associated with significantly increased length of stay, total charges, admission-to-procedure time, and mortality compared to those on weekdays. Our findings suggest that the development of nationwide programs to standardize care and weekend case management for THA patients can potentially help reduce health care costs, improve operative outcomes, and reduce the discrepancy between weekend and weekday surgeries.
Keywords: total hip arthroplasty; weekend effect; weekday